решите уравнение: а) (2x-1)+(-x+5)=2 б)(43-12x)-(-7x+33)=-2 в) (-3x+1)+(7-2x)=16 г)(2x-10)-(3x-4)=6 ЗАРАНЕЕ ОГРОМНОЕ СПАСИБО!!!!!!!!!!

1

Ответы и объяснения

2013-03-06T08:20:22+00:00

(2x-1)+(-x+5)=2      2x-1-x+5=2   2x-x=2-5   x=-3        (43-12x)-(-7x+33)=-2     43-12x+7x-33=-2    -12x+7x=-2+33-43    -5x=-45+33   -5x=-12   x=2.4         (-3x+1)+(7-2x)=16      -3x+1+7-2x=16         -3x-2x=16-1-7      -5x=8    x=-1.6                     (2x-10)-(3x-4)=6     2x-10-3x+4=6     2x-3x=6-4+10         -x= 12    x=12